Hubungan Dukungan Sosial dan Efikasi Diri dengan Kualitas Hidup Pasien Hemodialisis - Dinda Rahma Maghfiroh; Brune Indah Yulitasari; Allama Zaki Almubarok (STIKES Bina Usada Bali, 2026)
Background: Chronic Kidney Disease (CKD) is a long-term condition marked by a steady loss of kidney function, influencing multiple facets of patients’ daily experiences, especially those undergoing hemodialysis. The escalating prevalence of CKD in Indonesia calls for efforts to identify determinants that can enhance patients’ quality of life. This study investigated how social support and self-efficacy relate to the quality of life of CKD patients receiving hemodialysis at Panembahan Senopati Regional Hospital, Bantul. Methods: A quantitative approach with a cross-sectional correlational design was applied, involving 192 participants recruited via purposive sampling. Data were gathered using a demographic form, the Multidimensional Scale of Perceived Social Support (MSPSS), the CKD Self-Efficacy Scale (CKD-SE), and the WHOQOL-BREF. Results: Analysis using Spearman's rank correlation indicated a significant positive association between social support and quality of life (r = 0.660; p < 0.001) and between self-efficacy and quality of life (r = 0.818; p < 0.001). Conclusion: Greater social support and self-efficacy in patients undergoing hemodialysis are associated with an improved quality of life.